Maturity Level On Computer-Based Accounting Systems: The Case of Indonesian Small Medium Enterprises - Muhammad Noor Ardiansah; Indah Anisykurlillah (Journal of Management and Business Environment (JMBE), 2020)
This study aims to provide the empirical facts of the maturity level of computer-based accounting systems adopted by small and medium enterprises (SMEs) in Indonesia. This study was motivated by the limited research on the antecedent of adoption of computer-based accounting systems in SMEs. A survey conducted to SMEs in Semarang using questionnaire. The data was analyzed using correlation test. The results show the maturity level of the SMEs accounting system is at the third level (defined), which means that the accounting system development activities have been determined but are not yet optimal. Key maturity activities that are related significantly are planning and organization, business process management, risk management, and problem management, as well as system standardization and measurement. The results of this study contribute to the government to create a strategy for increasing adoption by strengthening the SMEs system maturity.